ECOTOXICOLOGICAL EFFECTS OF IBUPROFEN (NSAID) ON FRESHWATER SHRIMP, Gammarus pulex COLLECTED FROM BRAMHAM ESTATE, LEEDS, WEST YORKSHIRE UNITED KINGDOM. - Ogunbanwo, O. M. A; Kay, P.; Brown, L.; Okeowo, T. A. (Nigerian Journal of Fisheries, 2018)
An increasing number of pharmaceuticals have been found in the aquatic environment and the issue has become of human and environmental health concern. Many pharmaceuticals are not fully degraded in wastewater treatment plants (WWTPs) and are continuously released into the aquatic environment resulting in low range concentrations (?gL-1 ) in the receiving waters. Ibuprofen is a widely used non-steroidal anti-inflammatory drug (NSAID) and is persistent in the aquatic environment. This pharmaceutical has been frequently reported in wastewater effluents, surface waters, groundwater and even drinking water. In this study, the ecotoxicological effects of ibuprofen on the growth, feeding, and mortality of freshwater shrimp, Gammarus pulex was investigated in a laboratory experiment. Seventy-five (75) male G. pulex were assigned at random among five experimental groups (three treatments: 420.8 ngL-1 , 2629.6 ngL-1 and 4838.4 ngL-1 and two controls: negative and solvent controls) in a static-renewal bioassay for four weeks, with 100% renewal of water and the respective treatments weekly. The results showed that exposure of G. pulex to environmentally relevant concentrations of ibuprofen had no significant effects on feed intake (p=0.36), growth rate (p=0.09), and mortality (p=0.53). However, further investigations on the multigeneration effects of ibuprofen on G. pulex may be needed to confirm that, ibuprofen effects on G. pulex is non-consequential.